Zonadhesin Is Essential for Species Specificity of Sperm Adhesion to the Egg Zona Pellucida - Tardif, Steve (American Society for Biochemistry and Molecular Biology, 2010)
Interaction of rapidly evolving molecules imparts species specificity to sperm-egg recognition in marine invertebrates, but it is unclear whether comparable interactions occur during fertilization in any vertebrate species. In mammals, the sperm acrosomal protein zonadhesin is a rapidly evolving molecule with species-specific binding activity for the egg zona pellucida (ZP). Here we show using null mice produced by targeted disruption of Zan that zonadhesin confers species specificity to sperm-ZP adhesion. Sperm capacitation selectively exposed a partial von Willebrand D domain of mouse zonadhesin on the surface of living, motile cells. Antibodies to the exposed domain inhibited adhesion of wild-type spermatozoa to the mouse ZP but did not inhibit adhesion of spermatozoa lacking zonadhesin. Zan(−/−) males were fertile, and their spermatozoa readily fertilized mouse eggs in vitro. Remarkably, however, loss of zonadhesin increased adhesion of mouse spermatozoa to pig, cow, and rabbit ZP but not mouse ZP. We conclude that zonadhesin mediates species-specific ZP adhesion, and Zan(−/−) males are fertile because their spermatozoa retain adhesion capability that is not species-specific. Mammalian sperm-ZP adhesion is therefore molecularly robust, and species-specific egg recognition by a protein in the sperm acrosome is conserved between invertebrates and vertebrates, even though the adhesion molecules themselves are unrelated.